2020
DOI: 10.3389/fmed.2020.00115
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Macrophages in Chronic Cholangiopathies Featuring Biliary Fibrosis: An Attractive Therapeutic Target for Orphan Diseases

Abstract: Cholangiopathies are a heterogeneous group of chronic liver diseases caused by different types of injury targeting the biliary epithelium, such as genetic defects and immune-mediated attacks. Notably, most cholangiopathies are orphan, thereby representing one of the major gaps in knowledge of the modern hepatology. A typical hallmark of disease progression in cholangiopathies is portal scarring, and thus development of effective therapeutic approaches would aim to hinder cellular and molecular mechanisms under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 82 publications
(102 reference statements)
0
15
0
Order By: Relevance
“…Between the two published gene signatures there is one overlapping gene, TNFRSF12A . Interestingly, IL32 has been previously reported as the top up-regulated liver transcript in NAFLD 39 . We also checked the 25-gene signature from 10 in our cluster analysis, with 17 of the 25 genes corresponding to cluster 2 ( CCL20 , CFAP221 , DTNA , DUSP8 , IL32 , ITGBL1 , STMN2 , TNFRSF12A ), cluster #3 ( COL1A1 , COL1A2 , LTBP2 , PDGFA , RGS4 , THY1 ) and cluster 5 ( AKR1B10 , CLIC6 , TYMS ) of up-regulated genes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Between the two published gene signatures there is one overlapping gene, TNFRSF12A . Interestingly, IL32 has been previously reported as the top up-regulated liver transcript in NAFLD 39 . We also checked the 25-gene signature from 10 in our cluster analysis, with 17 of the 25 genes corresponding to cluster 2 ( CCL20 , CFAP221 , DTNA , DUSP8 , IL32 , ITGBL1 , STMN2 , TNFRSF12A ), cluster #3 ( COL1A1 , COL1A2 , LTBP2 , PDGFA , RGS4 , THY1 ) and cluster 5 ( AKR1B10 , CLIC6 , TYMS ) of up-regulated genes.…”
Section: Discussionmentioning
confidence: 97%
“…6 underscores previously described molecular influences on the fibrotic microenvironment 12 . Molecular cues from damaged hepatocytes activate aberrant intercellular cross-talk between heterogenous monocyte-derived macrophage subpopulations 39 and hepatic cells to orchestrate a progressive fibrotic niche 12 , 19 , 23 . Our data identified potential key drivers of these pathways within the deconvoluted macrophage, cholangiocyte, HSC, and hepatocyte specific genes in the signature.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of β‐catenin signaling is responsible for a lower local concentration of β‐catenin‐dependent profibrotic chemokines around the biliary structures resulting in a reduction of the pericystic inflammatory infiltrate. In turn, the reduced number of inflammatory cells account for a diminished secretion of cytokines trophic for the biliary epithelium, with a consequent reduction in the size of the cysts paralleled by a reduced deposition of fibrosis 49,50 …”
Section: Discussionmentioning
confidence: 99%
“…CHF is a heterogeneous cholangiopathy that frequently manifests as part of cilia‐related syndromic disorders, such as autosomal recessive polycystic kidney disease (OMIM #263200), Meckel‐Gruber syndrome (OMIM #249000), Joubert syndrome (OMIM #213300), Bardet‐Biedl syndrome (OMIM #209900), nephronophthisis (NPHP) (OMIM #256100), or oral‐facial‐digital syndrome (OMIM #311200), indicating that ciliary dysfunction which underpins the ductal plate remodeling abnormalities in these disorders can secondarily lead to progressive fibrogenesis in the portal tract 10,33,34 . Indeed, work by several groups, including ours, have demonstrated that defective bile duct morphogenesis gives rise to damaged and immature cholangiocytes, which secrete different profibrotic cytokines (Tgfb1) and growth factors (Ctgf) that promote cell proliferation and fibrogenesis in the surrounding tissue 7,35,36 .…”
Section: Discussionmentioning
confidence: 99%